STUDI LITERATUR TENTANG FENOMENA BULLYING DI JAWA TIMUR - Habsy, Bakhrudin All; Alamsyah, Aisyah Dzakia; Maula, Anjany I’anatu (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This research was conducted by researchers using qualitative methods with a literature study design. Researchers chose various sources related to the topic and problem formulation that will be discussed in this research. This research focuses on the main concept of bullying and bullying cases that occur in the educational sphere, such as cases that occur in middle and high schools. The results of this research show that self-esteem does influence bullying behavior and changes in the number of cases that occur in Indonesia, especially in the province of East Java.